2009
DOI: 10.1088/1464-4258/11/12/125409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lanthanoid organometallic compounds on holographic storage characteristics of doped PQ/poly(hydroxyethyl methacrylate-co-methyl methacrylate) hybrids

Abstract: In this research, we fabricate and characterize lanthanide organometallic compounds and 9,10-phenanthrenequinone (PQ) co-doped poly(2-hydroxyethyl methacrylate-co-methyl methacrylate) photopolymers for holographic recording. Five different lanthanoid (Ce 3+ , Nd 3+ , Er 3+ , Yb 3+ and Lu 3+) organometallic compounds, one at a time, is co-doped with PQ in a poly(HEMA-coMMA) matrix, respectively. Holographic experiments demonstrate that lutetium organometallic compounds and a PQ co-doped poly(HEMA-coMMA) photopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…The summation of the square roots of the diffraction efficiency as a function of the exposed energy forms a running curve of the cumulative grating strength (Figure 4). It can be expressed as where n is total number of holograms recorded for a total exposed energy density of E (J/cm 2 ) 3, 11, 12, 18. By curve fitting with the function the saturation value C sat (M#) of the curve gives the dynamic range of the material, and E t gives the exposed energy constant of the material 3, 18.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The summation of the square roots of the diffraction efficiency as a function of the exposed energy forms a running curve of the cumulative grating strength (Figure 4). It can be expressed as where n is total number of holograms recorded for a total exposed energy density of E (J/cm 2 ) 3, 11, 12, 18. By curve fitting with the function the saturation value C sat (M#) of the curve gives the dynamic range of the material, and E t gives the exposed energy constant of the material 3, 18.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we have found that 9,10‐phenanthrenequinone (PQ)‐doped PMMA serves as an excellent holographic recording material 3, 10–12. The grating in such systems is formed through photoreactions, with the photoproduct featuring one methyl methacrylate (MMA) unit attached to one PQ derivative3; notably, however, the limited availability of PQ in the PMMA/PQ system restricts the dynamic range (M#) of holographic data storage.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Yu-Fang Chen improved the holographic properties of PQ/PMMA polymers by introducing five different lanthanide metal–organic compounds [ 116 ] (Ce 3 + , Nd 3+ , Er 3+ , Yb 3+ , and Lu 3+ ). The experimental results showed that the doping of PQ/PMMA photopolymer systems by lanthanide metal–organic compounds could improve the material’s diffraction efficiency and dynamic range.…”
Section: Origins Of Pq/pmma and Performance Improvement Measuresmentioning
confidence: 99%